Pemanfaatan Fasilitas Belajar di Sekolah, Displin, Minat, dan Hasil Belajar IPS - Arsyid; Lasim Muzammil (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2020)
This research is motivated by the low utilization of learning facilities in schools, interests and discipline, this is seen from the lack of students utilizing learning facilities in schools such as students not going to the library during empty hours, lacking use of books in the library as a reference for learning, lack of discipline such as often being late in entering class, often in and out of the learning process and low student interest in learning as there are still chatting in class, many students who just play and pay less attention to the teacher during the learning process. This study aims to determine (1) The effect of the use of learning facilities in schools, discipline, and mutual interest in social studies learning outcomes at SMP Negeri 9 Baubau. (2) The effect of the use of learning facilities in schools on the results of social studies learning at SMP Negeri 9 at SMP Negeri 9 Baubau. (3) The effect of discipline on social studies learning outcomes in SMP Negeri 9 Baubau and (4) The influence of interest in learning outcomes at social studies at SMP Negeri 9 Baubau. This type of research is a quantitative descriptive survey approach. The study population was 85 and the entire population was determined as the study sample. The results showed: (1) there was an influence jointly or simultaneously the use of learning facilities in schools, discipline, and interest in social studies learning outcomes, (2) there was an influence of the use of learning facilities in schools on social studies learning outcomes, (3) there was an influence discipline in the learning outcomes of social studies, and (4) there is an influence of interest in learning outcomes in social studies.